The psychometric properties of childhood physical and sexual abuse measures in two Canadian samples of youth and emerging adults - Vanessa De Rubeis; Lil Tonmyr; Masako Tanaka; Tracie Afifi; Nicole Catherine; Ana Osorio; Harriet L. MacMillan; Andrea Gonzalez (PLoS ONE, 2025)
Introduction Child maltreatment is prevalent in Canada; how we measure it varies. The objective of the current study was to examine the psychometric properties of the Childhood Experiences of Violence Questionnaire Short Form (CEVQ-SF) physical and sexual abuse measures and of the Canadian Community Health Survey (CCHS) 2-item sexual abuse measure, compared with the Childhood Trauma Questionnaire (CTQ) in two samples of adolescents and young adults. Methods Retrospective, self-reported child abuse history was collected in the British Columbia Healthy Connections Project (BCHCP) and in the Well-Being and Experiences (WE) Study. Internal consistency, criterion validity, and construct validity were examined. Results Across both samples, the prevalence of child physical abuse (CPA) and child sexual abuse (CSA) ranged from 12.5% to 41.4% and from 5.8% to 34.3%, respectively. Internal consistencies were good-to-acceptable for CPA using the CEVQ-SF in the BCHCP (α = 0.83) and the WE Study (α = 0.79) and for CSA using the CEVQ-SF in the WE Study (α = 0.68). For CPA, in both studies, the highest agreement—moderate-to-fair—was between CEVQ-SF severe CPA and CTQ moderate CPA: κ=0.63 (BCHCP) and κ= 0.35 (WE Study). For CSA, agreement with CTQ moderate cut-offs was substantial in the BCHCP (κ=0.77) and fair in the WE Study (κ=0.37). Discussion Our findings support current and future use of the CEVQ-SF for CPA, and for CSA, using both the CEVQ-SF and the CCHS-CSA measure, given that they had good psychometric properties when administered to two samples of adolescents and young adults.